2007
DOI: 10.1088/0004-6256/135/1/232
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Hydrogen Properties of Active Galactic Nuclei Host Galaxies: H I in 16 Nuclei of Galaxies (Nuga) Sources

Abstract: We present a comprehensive spectroscopic imaging survey of the distribution and kinematics of atomic hydrogen (H i) in 16 nearby spiral galaxies hosting low luminosity active galactic nuclei (AGN), observed with high spectral and spatial resolution (resolution: ∼20 , ∼5 km s −1 ) using the NRAO Very Large Array (VLA). The sample contains a range of nuclear types ranging from Seyfert to star-forming nuclei, and was originally selected for the NUclei of GAlaxies project (NUGA)-a spectrally and spatially resolved… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
69
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(85 citation statements)
references
References 75 publications
(109 reference statements)
16
69
0
Order By: Relevance
“…The majority of the Seyferts with close companions show signs of recent nuclear star formation, leading Storchi‐Bergmann et al to suggest that the pure Seyfert spectrum emerges after the main starburst has faded. A similar evolutionary scenario was suggested by Haan et al (2008), whereby low‐luminosity AGN precede Seyferts after a merger, based on high fractions of the former, but few of the latter in a sample of galaxies with disturbed H i discs. Delays are also implied by the intermediate colours and spectral characteristics of AGN hosts, indicating at least ∼100 Myr between the decline of star formation and black hole activity (Schawinski et al 2009).…”
Section: Introductionsupporting
confidence: 69%
“…The majority of the Seyferts with close companions show signs of recent nuclear star formation, leading Storchi‐Bergmann et al to suggest that the pure Seyfert spectrum emerges after the main starburst has faded. A similar evolutionary scenario was suggested by Haan et al (2008), whereby low‐luminosity AGN precede Seyferts after a merger, based on high fractions of the former, but few of the latter in a sample of galaxies with disturbed H i discs. Delays are also implied by the intermediate colours and spectral characteristics of AGN hosts, indicating at least ∼100 Myr between the decline of star formation and black hole activity (Schawinski et al 2009).…”
Section: Introductionsupporting
confidence: 69%
“…Previous studies have detected H i gas in LINERs (Haan et al 2008;Geréb et al 2013Geréb et al , 2015. Haan et al (2008) found the mean H i mass of seven LINERs to be ∼ 10 10 M , which is comparable to the H i masses of the most massive LIERs in the spectroscopic sample. Figure 5, classification lines are included on each subplot.…”
Section: J2120-39supporting
confidence: 52%
“…The stellar mass is derived from the 2MASS K-band images and the K-band mass-to-light ratios (Section 3.2). For the cold gas mass, we use the H i mass of 4.7 × 10 10 M for NGC 1961 (Haan et al 2008), and we estimate the H i mass of about 2 × 10 10 M for NGC 6753 (Haynes & Giovanelli 1984). Since both galaxies are located in poor groups (Fouque et al 1992), the baryon mass of these galaxies should also be included in the baryon budget.…”
Section: Baryon Mass Fractionmentioning
confidence: 99%